Intrauterine Growth Retardation Complicated by Biermer’s Disease: An Observation in Togo - Essohana Padaro; Baguilane Douaguibe; Kossi Agbétiafa; Irénée Kueviakoe; Ahoefa Vovor (Case Reports in Hematology)
Objective. To report the first case in Togo of Biermer’s disease associated with intrauterine growth retardation (IUGR) in a 39-year-old pregnant woman. Observation. The patient with phenotype AA, born on 20/02/1978, G2P0 (a spontaneous abortion at 3 months), was referred to hematology on 17th March 2017 for anemia at 26 weeks of amenorrhea (WA). She had received martial treatment with ferrous fumarate 66 milligrams daily. At 26 weeks, the uterine height was 16 centimeters, and there was good fetal vitality. During ultrasound, there was a harmonious development of the fetus, but it was lower than that for the gestational age at 10th percentile based on fetal biometry, and anemia was at 65 g/l. She was then referred to hematology where she was found to have pancytopenia with macrocytic aregenerative anemia at 47 g/l (MCV at 109 fl), neutropenia at 1.02 g/l, and thrombocytopenia at 58 g/l. The myelogram found megaloblastosis at 53%, collapsed serum B12 vitamin at 61.7 pg/ml, normal serum folate at 9.9 ng/ml, increased serum homocysteine to 51.44 μmol/l, and elevated LDH. The search for intrinsic anti-factor antibodies was positive. Digestive endoscopy noted fundal atrophy. The patient was given vitamin B12 injection; at the 7th day, hemoglobin was observed at 94 g/l, then a normalization of the blood count after 3 weeks, and a good evolution of the pregnancy with delivery at 38 WA of a newborn, female, weighing 1960 g with 500 grams of placenta, with a size of 40 cm, and a cranial perimeter of 29 cm. The child had stunted weight growth (at 16 months; weight = 7 kg; height = 69 cm). Conclusion. Biermer’s disease as a maternal cause of IUGR and infantile hypotonia is a reality in Togo. It requires management in patients and especially during pregnancy to avoid neurological complications in children born from mothers with this disease.